Procalcitonin as a prognostic marker of patients with acute ischemic stroke. Issue 7 (20th March 2020) - Yan, Ling; Wang, Shuling; Xu, Lanlan; Zhang, Zhen; Liao, Pu
Abstract: Background: The information on mortality after an acute stroke patient is still limited. Objectives: The aim of this study was to investigate the prognostic potential of procalcitonin (PCT) serum levels in acute ischemic stroke. Methods: A total of 748 patients were enrolled in this study. Prognostic potential of PCT was evaluated by Kaplan‐Meier analysis and multivariable Cox hazard regression analyses. Results: Procalcitonin levels were found to be significantly higher in acute ischemic stroke patients who died in 30 days than those who survived. Univariate logistic regression analysis showed that PCT was significantly associated with 30‐day mortality, and Cox regression analysis revealed that PCT was a strong predictor of 30‐day overall mortality. Kaplan‐Meier analysis revealed that overall cumulative 30‐day mortality was significantly higher in those with PCT levels >1.5 ng/mL when compared to those with PCT levels <1.5 ng/mL. Conclusions: Procalcitonin is a significant independent prognostic marker of 30‐day mortality after the one set of acute ischemic stroke.